RELIGIOUS MODERATION : AGAINST INTOLERANCE AND DERADICALIZATION - I Nyoman Alit Putrawan; I Made Gede Nesa Saputra; Kadek Agus Wardana (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
Conflict between religious communities is a sensitive matter that often occurs. This is due to truth claims about various practices that tend to be different from the teachings of the religion adhered to. Indonesia as a country that embraces pluralism does not escape the turmoil of religious conflicts that characterize the life of the nation, so that it has an impact on the loss of tolerance between people and tends to bring up radical principles and coercion of one belief. To produce valid and reliable data, this paper uses a qualitative writing style. In producing logical data, this paper performs several stages of data sorting in the form of: 1). Data reduction, 2). Display data, 3). Verifying data, and 4). Interpret research data. In its presentation, measurable analysis becomes the foundation in processing the data obtained. The perfection of this paper cannot be separated from the library technique carried out by exploring the existing literature in Google Scholar. Truth claims that are too radical tend to foster a sense of intolerance in a nation, this situation will be used by terrorist elements to build a division of the state through religious cloaks. This situation became the center of attention of the Indonesian government so that a program called